Kewirausahaan Kelompok Wanita Tani Sebagai Penggerak Pemberdayaan Masyarakat di Kampung Eduwisata Hanjeli Desa Waluran Mandiri Kecamatan Waluran Kabupaten Sukabumi - Ashrul Tsani; Neneng Kartika Rini; Iwan Rizal Setiawan (Paspalum: Jurnal Ilmiah Pertanian, 2021)
The decrease of the community’s carrying capacity in Waluran Mandiri Village in the utilization of potential land resources has resulted in the change of abandoned agricultural land into illegal mining. This sad reality is also saddled with the large number of women who become migrant workers abroad. The hanjeli’s cultivation as an effort to empower the community has been initiated with the concept implementation of the Hanjeli Eduwisata Village. The purpose of this study is to describe the process of woman farmer groups’ empowerment in Hanjeli Eduwisata Village, and to analyze the business of hanjeli products carried out through the groups’ entrepreneurial activities. The study used a survey method with purposive sampling of a group of woman farmers. The data were then analyzed using descriptive quantitative method by presenting tabulations and diagrams. The results showed that the community empowerment in Hanjeli Eduwisata Village was pioneered by woman's farmer group named Mekar Mandiri through an entrepreneurial process. namely: establishing business working groups and entrepreneurship training, forming farmer groups, revitalizing abandoned land, and carrying out entrepreneurship training programs regarding cultivation techniques, product processing as well as marketing of Hanjeli products. The average production of Hanjeli was low due to intercropping on an average land area of 0.43 ha, Hanjeli farming still provided benefits to Mekar Mandiri woman farming group in two growing seasons per one year. Likewise, the the business of processed Hanjeli products by KWT Mekar Mandiri showed a positive profit margin.